LINGUOCULTROLOGICAL ASPECTS OF THE ORIGINAL TRANSLATION IN FOREIGN LANGUAGE TRANSLATORS - Abdurashidova, Nilufar (Журнал иностранных языков и лингвистики, 2023)
In our article, it is important that tourist centers have a high level of knowledge and constantly improve their knowledge and professional skills, culture, and language, with a special emphasis on history, geography, art and architecture, economics, politics, religion, and sociology. One of the most important factors is that travelers-translators know the technology of human information selection and can successfully cooperate with foreign and domestic tourists in their best activities.